Identification and selection of yeast with functional properties for future application in soft paste cheese. (April 2020) - Merchán, Almudena V.; Benito, María José; Galván, Ana Isabel; Ruiz-Moyano Seco de Herrera, Santiago
Abstract: This study investigated the yeast community in traditional soft cheese from the Extremadura region to be able to establish possible beneficial properties for human health. A total of 149 yeast isolates were characterised at strain level using the ISSR-PCR technique with the primer (GTG)5 . Forty-three different genetic profiles were obtained, and the yeasts were grouped into 12 species allowing their typification at strain level. Regarding probiotic tests, 54 strains were selected for the study of probiotic properties based on genetic profile and origin. All of them showed adequate tolerance to the most restrictive stomach and bile salts conditions, although strains of Kluyveromyces lactis and Pichia fermentans presented better ability to survive to these stresses. P. fermentans was also the species that showed better antioxidant, auto-aggregation and hydrophobicity capacity, at the same time as antimicrobial activity, followed by Kluyveromyces sp. strains. Thus, considering the probiotic characteristics studied, 15 strains, P. fermentans 1826, 1865, 1859, 1911, 1913, 1916 and 1938; P. kudriavzevii 1801, 1809 and 1832; K. marxianus 1886, 1917 and 1919; D. hansenii 1860; and Y. lipolytica 1961, are promising potential probiotic candidates for developing a functional cheese. Highlights: Yeasts from traditional cheese were examined for probiotic properties. ISSR-PCR technique allowed yeast typification at strain level. K . lactis and P. fermentans were better adapted to gastrointestinal stresses. K. lactis and P. fermentans presented higher antioxidant, auto-aggregation and hydrophobicity capacity. 15 strains were selected as probiotic candidates for developing a functional cheese.